Evaluation of the benefit and use of multidisciplinary teams in the treatment of head and neck cancer. (August 2016) - Licitra, Lisa; Keilholz, Ulrich; Tahara, Makoto; Lin, Jin-Ching; Chomette, Pauline; Ceruse, Philippe; Harrington, Kevin; Mesia, Ricard
Highlights: Treatments for patients with head and neck cancer are highly complex. Multidisciplinary teams (MDTs) are therefore needed for optimal patient care. Country-specific guidance regarding MDTs are somewhat variable. Expert practical advice to facilitate universal establishment of MDTs is provided. Summary: Given the complexities of multimodality treatment for patients with head and neck cancer, the rationale for the use of multidisciplinary teams (MDTs) to define individual optimal treatment strategies on a per-patient basis is apparent. Increased use of guideline-directed approaches, reduced time to treatment and improved outcomes, which result from use of an MDT approach in head and neck cancer, have been documented. A discussion of these recent advances, as well as presentation of available country-specific guidance on the roles and responsibilities of team members, supports the creation of similar local-language recommendations for the treatment of patients with head and neck cancer. Finally, expert practical advice on the implementation of MDTs may enable the establishment of the MDT approach more universally around the world.